Reformulating National Defense Policy Through Artificial Intelligence: Enhancing Strategic Decision Making and Ethical Governance - Hidayatullah, Syarif; Supriyadi, Asep Adang; Purwanto, Ignatius Eko Djoko; Saputro, Guntur Eko (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the role of artificial intelligence (AI) in reformulating national defense policy to enhance strategic decision making. Utilizing a qualitative, descriptive methodology supported by literature reviews and expert interviews, the research analyzes how AI can support data driven policy making, improve risk assessment, and optimize military resources. The research aims to examine how AI can improve operational efficiency, predictive analysis, and response capability against emerging threats. The study applies SWOT and Technology Readiness Level (TRL) frameworks to assess the strategic integration of AI in defense systems. Findings highlight both the opportunities and ethical concerns associated with AI adoption. The findings suggest that AI significantly supports data driven decision-making, enhances risk assessment, and optimizes military resource management. However, ethical and accountability concerns persist, necessitating the inclusion of explainable AI frameworks. The research proposes a structured model for ethical and inclusive AI governance and underscores the need for international cooperation in defense AI development.